NURSING CARE OF AIRWAY CLEARANCE INEFFECTIVE IN CHILDREN WITH PNEUMONIA: A CASE REPORT - Sulpat, Emuliana; Mardhika, Amellia; Fadliyah, Lailatul; Tyas, Anestasia Pangestu Mei; Harianto, Susilo; Sari, Adhelia Fadilla (Journal of Vocational Nursing, 2023)
Introduction: pneumonia is one of the acute lower respiratory tract infectious diseases with symptoms of cough and accompanied by shortness of breath caused by  infectious agents such as viruses,  bacteria, mycoplasma  and  aspiration of foreign  substances  , in the form of pneumonia accompanied by exudation and consultation. Airway clearance is not effective in many pneumonia patients.  The aim of the study to get an overview and experience in providing pediatric nursing care with airway clearance is not effective in pneumonia. Methods: this research uses qualitative method type case study with nursing process approach. The subjects in this study amounted to 3 patients diagnosed with pneumonia with nursing problems of ineffective airway clearance in the Orchid Room of RSUD Ibnu Sina Gresik in research data collection techniques, namely interviews, observations and documentation studies. Results: based on the main assessment of the three patients, it was found that the patient had a cough and shortness of breath The nursing diagnosis that emerged was   that   airway clearance was ineffective associated with retained secretions.   The focus intervention carried out is teaching effective cough 822and doing chest physiotherapy. After 3 days of nursing action by the researcher each obtained an evaluation on the third day of cases 1, 2 and 3 the problem was partially resolved.  Conclusions: The selection of intervention is an important factor when conducting airway clearance nursing care is not effective to prevent  contraindications so as to  speed up the patient's recovery.